Factors Influencing Handwriting Development among Preschool Children: A Systematic Review - Achymy, Zati Izny; Kadar, Masne; Razaob, Nor Afifi; Wan Yunus, Farahiyah (UI Scholars Hub, 2022)
Handwriting development is essential for academic performance, yet the research on the factors contributing to it is scant. This systematic review aimed to provide a comprehensive overview of the factors contributing to handwriting development among preschool children that may benefit public health knowledge, especially among teachers, parents, and therapists. A systematic search was conducted using four databases: PubMed, ERIC, CINAHL, and Google Scholar. During the preliminary search, 565 relevant studies were found. Screening, review selection, and characterization were performed based on the inclusion and exclusion criteria. The inclusion criteria included preschool children, quantitative, written in English, and published in January 2012 – January 2022. The exclusion criteria were studies involving children with specific diagnoses. A consensus agreement was obtained, and ten studies were eventually selected for the comprehensive review. Executive function, letter knowledge, motor skills, and writing surface were identified. These factors indicated that handwriting was not an independent process, as its acquisition involved numerous components. This systematic review confirmed that executive function, letter knowledge, motor skills, and writing surface influenced handwriting development. More randomized controlled trials should be conducted to provide more conclusive and exhaustive evidence.